2015
DOI: 10.16943/ptinsa/2015/v81i2/48104
|View full text |Cite
|
Sign up to set email alerts
|

Small and Macromolecules Crystallization Induced by Focused Ultrafast Laser

Abstract: The structure based drug design has been limited by various factors that include protein crystallization, which is one of the most challenging tasks in this area. It has been proved unequivocally that X-ray crystallography is highly trusted technique for three dimensional structure determination of small-and macro-molecules. It has provided the definite solution for several key areas such as structure based drug design, site directed mutagenesis and elucidation of enzyme mechanisms. In X-ray crystallography, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…In 2014 Clair et al proposed a broader definition of NPLIN to include all experiments in which intense light induces nucleation in supersaturated solutions or supercooled liquids without the addition of seeds and in which the substance that nucleates is chemically identical to the original substance . This includes nucleation with focused femtosecond laser pulses, with focused continuous-wave (cw) laser beams, and with irradiation through the air/solution interface. , With focused laser pulses, the higher peak intensities can induce shockwaves and cavitation bubbles, opening up additional pathways to nucleation. With focused cw laser beams, photon pressure can induce solute–cluster aggregation in the beam focus, leading to liquid–liquid phase separation and nucleation even in undersaturated solutions .…”
Section: Introductionmentioning
confidence: 99%
“…In 2014 Clair et al proposed a broader definition of NPLIN to include all experiments in which intense light induces nucleation in supersaturated solutions or supercooled liquids without the addition of seeds and in which the substance that nucleates is chemically identical to the original substance . This includes nucleation with focused femtosecond laser pulses, with focused continuous-wave (cw) laser beams, and with irradiation through the air/solution interface. , With focused laser pulses, the higher peak intensities can induce shockwaves and cavitation bubbles, opening up additional pathways to nucleation. With focused cw laser beams, photon pressure can induce solute–cluster aggregation in the beam focus, leading to liquid–liquid phase separation and nucleation even in undersaturated solutions .…”
Section: Introductionmentioning
confidence: 99%
“…This method was then taken up by various laboratories and has grown rapidly in recent years, with some variations on the setup / laser. However, depending on the authors, different names to the experiment were given, leading to different abbreviations (NPLIN 1 , laser irradiation 2 , LIGHT 3 , laser-induced crystallization 4 , optical breakdown 5 , photon pressure 6 , LIN (Laser-Induced Nucleation) 7 , laser trapping crystallization 8 , optical trapping 9 , laser-induced cavitation 10 , laser shock wave induced crystallization 11 , light induced crystallization 12 , LIPS 13 , LIPSaN 14 , ...) often referring to a putative mechanism. For a better understanding of this method and thus to contribute to the broadening of its use, Clair et al 15 extended the definition of NPLIN to any nucleation experiment of a supersaturated solution crystallizing after being illuminated by a laser beam.…”
Section: Introductionmentioning
confidence: 99%
“…This method was then taken up by various laboratories and has grown rapidly in recent years, with some variations on the setup/laser. However, depending on the authors, different names to the experiment were given, leading to different abbreviations (NPLIN, 1 laser irradiation, 2 LIGHT, 3 laser-induced crystallization, 4 optical breakdown, 5 photon pressure, 6 LIN (laser-induced nucleation), 7 laser trapping crystallization, 8 optical trapping, 9 laserinduced cavitation, 10 laser shock wave-induced crystallization, 11 light-induced crystallization, 12 LIPS, 13 LIPSaN,. 14 ) often referring to a putative mechanism.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, we have crystallized both small biomolecules and a protein (lysozyme) using a femtosecond laser (λ = 800 nm, 60 fs pulse duration, 5.2 MHz repetition rate, 300 mW average power) 14 . This work showed that laser-induced crystallization is highly useful in obtaining crystals of small molecules, including chalcone compounds, which are otherwise difficult to crystallize by conventional crystallization methods 14 . We have also used simple but highly effective nucleants with a CW Nd:YAG (λ = 1064 nm) laser to crystallize NaCl, KCl, glycine, aspartic acid, and histidine amino acids, and lysozyme protein 15 .…”
Section: Introductionmentioning
confidence: 99%